ANALISIS KESALAHAN BAHASA ANAK USIA 4 TAHUN DILIHAT DARI TATARAN FONOLOGI - Mulyani, Wina; Mustika, R Ika; Lestari, Riana Dwi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The language that was first recognized by children is the language of the mother. Children's language development depends on the language taught by a mother. In addition, children easily catch or imitate language from their environment. However, in addition to the development of the vocabulary that is owned by a child, there are also some mistakes that occur when children speak the language they just heard. This study aims to determine the mistakes made by children at the age of 4 years at the level of phonology. In the phonological level regarding language sounds, word errors spoken by children there are some phoneme changes such as / r / to / l /, or there is an increase or decrease in phonemes in one word. The data obtained by researchers to determine children's language errors namely when the child sings. The method used by listening, note, and record. The data obtained will be described and classified. In the golden age, the role of parents is very important to improve the vocabulary owned by children, because at that time the initial development is more important than the subsequent development, when children are influenced by learning and experience. From the analysis there were 25 errors in phoneme / r / be / l / replacement, 23 errors in phoneme / s / become / c / changes, there were 6 errors in phoneme / h /, / b /, and / t / phonemes, and there were phonemes added / h / from the word "again" to "lag".